Molecular findings from influenza A(H1N1)pdm09 detected in patients from a Brazilian equatorial region during the pandemic period - Oliveira, Maria José Couto (2014)
Thiago Moreno Lopes e Souza - Fundação Oswaldo Cruz. Centro de Desenvolvimento Tecnológico em Saúde. Rio de Janeiro, RJ, Brasil. Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta a informação no documento.